1993
DOI: 10.1113/jphysiol.1993.sp019459
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of intrahepatic innervation in caesium‐induced haemodynamic oscillations in the rat liver.

Abstract: SUMMARY1. Cs' was used to study the mechanisms involved in the induction of haemodynamic and metabolic oscillations in the isolated rat liver perfused by the portal vein. 5. The results show that the liver perfused by the portal vein has all of the components required to activate vascular synchrony including intrinsic neural input and responsive vasoactive cells. INTRODtTCTIONUntil relativelv recently, the regulation of blood flow through the intrahepatic portal and sinusoidal vasculature was generally thought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…19,25 Our data showing greater entry of transplanted cells in sinusoids along with more distal distribution of transplanted cells (to zone 2) raise the possibility of a difference in the vascular site(s) in hepatic sinusoids at which phentolamine and nitroglycerine exert their effects. Studies with isolated perfused liver preparations showed retention of phentolamine responsiveness, 26 which would indicate the presence of peripheral effects. Consideration of the periportal vascular anatomy, where communications between portal vein radicles, hepatic arterioles, and hepatic sinusoids exist, 31 should suggest that phentolamine influenced the periportal/sinusoidal vascular network because more transplanted cells entered the liver lobule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,25 Our data showing greater entry of transplanted cells in sinusoids along with more distal distribution of transplanted cells (to zone 2) raise the possibility of a difference in the vascular site(s) in hepatic sinusoids at which phentolamine and nitroglycerine exert their effects. Studies with isolated perfused liver preparations showed retention of phentolamine responsiveness, 26 which would indicate the presence of peripheral effects. Consideration of the periportal vascular anatomy, where communications between portal vein radicles, hepatic arterioles, and hepatic sinusoids exist, 31 should suggest that phentolamine influenced the periportal/sinusoidal vascular network because more transplanted cells entered the liver lobule.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we considered it appropriate to study whether transplanted cell distributions could be altered by the following drugs: phentolamine (␣-adrenergic blocker), labetalol (␣-and ␤-adrenergic blocker), the calcium channel blocker nifedipine, potent directly acting portal and splanchnic vasodilators, glucagon, nitroglycerine, and calcitonin gene-related peptide (CGRP). [20][21][22][23][24][25][26] Moreover, this pharmacologic approach provided us with opportunities to examine the effects of cell transplantation on the hepatic microcirculation. We used dipeptidyl peptidase IV (DPPIV)-deficient F344 rats for our studies.…”
mentioning
confidence: 99%